2009
DOI: 10.1523/jneurosci.3948-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Robo-2 Controls the Segregation of a Portion of Basal Vomeronasal Sensory Neuron Axons to the Posterior Region of the Accessory Olfactory Bulb

Abstract: The ability of sensory systems to detect and process information from the environment relies on the elaboration of precise connections between sensory neurons in the periphery and second order neurons in the CNS. In mice, the accessory olfactory system is thought to regulate a wide variety of social and sexual behaviors. The expression of the Slit receptors Robo-1 and Robo-2 in vomeronasal sensory neurons (VSNs) suggests they may direct the stereotypic targeting of their axons to the accessory olfactory bulb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 42 publications
(67 reference statements)
1
39
1
Order By: Relevance
“…Slits have been shown to bind with similar affinity to all of the Robo receptors using evolutionarily conserved binding residues (Brose et al, 1999;Morlot et al, 2007). However, in different systems, Slits mediate differing effects; for instance OSN axonal targeting is modulated by Slit1 and Slit2, but not by Slit3 (Prince et al, 2009). It will therefore be important to identify the molecules, such as coreceptors, that mediate such ligand specificity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Slits have been shown to bind with similar affinity to all of the Robo receptors using evolutionarily conserved binding residues (Brose et al, 1999;Morlot et al, 2007). However, in different systems, Slits mediate differing effects; for instance OSN axonal targeting is modulated by Slit1 and Slit2, but not by Slit3 (Prince et al, 2009). It will therefore be important to identify the molecules, such as coreceptors, that mediate such ligand specificity.…”
Section: Resultsmentioning
confidence: 99%
“…3B). Basal VSN axons are also misrouted in Slit1/Slit2 double-heterozygous mice, but not in Slit3 knockouts, thus establishing a role for Slit2, in addition to Slit1, in the proper targeting of VSN axons to the AOB (Prince et al, 2009). Although VSNs express both Robo1 and Robo2 receptors, only Robo2 appears to be essential for maintaining proper segregation of VSN axons in the AOB.…”
Section: Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous evidence has suggested a role of axon guidance molecules in the segregation of vomeronasal axons into their final position in the AOB (Knöll et al, 2001(Knöll et al, , 2003Walz et al, 2002;Prince et al, 2009), but until recently, no study had proposed molecular candidates for the regulation of maturation and fate choice of newly generated vomeronasal neurons. In a recent article published in The Journal of Neuroscience, however, Enomoto et al (2011) showed that Bcl11b/Ctip2, a zinc finger transcription factor involved in regulating corticofugal fate of deep-layered neocortical neurons , is crucial for maturation and fate determination of vomeronasal neurons, for establishing axonal projections to the AOB, and for correct layering of intrinsic AOB neurons.…”
mentioning
confidence: 99%